Immunity to HIV in Early Life - Muenchhoff, Maximilian; Prendergast, Andrew J.; Goulder, Philip Jeremy Renshaw (Frontiers in Immunology, 2014)
The developing immune system is adapted to the exposure to a plethora of pathogenic and non-pathogenic antigens encountered in utero and after birth, requiring a fine balance between protective immunity and immune tolerance. In early stages of life, this tolerogenic state of the innate and adaptive immune system and the lack of immunological memory render the host more susceptible to infectious pathogens like HIV. HIV pathogenesis is different in children, compared to adults, with more rapid disease progression and a substantial lack of control of viremia compared to adults. Plasma viral load remains high during infancy and only declines gradually over several years in line with immune maturation, even in rare cases where children maintain normal CD4 T-lymphocyte counts for several years without antiretroviral therapy (ART). These pediatric slow progressors also typically show low levels of immune activation despite persistently high viremia, resembling the phenotype of natural hosts of SIV infection. The lack of immunological memory places the fetus and the newborn at higher risk of infections; however, it may also provide an opportunity for unique interventions. Frequencies of central memory CD4+ T-lymphocytes, one of the main cellular reservoirs of HIV, are very low in the newborn child, so immediate ART could prevent the establishment of persistent viral reservoirs and result in “functional cure.” However, as recently demonstrated in the case report of the “Mississippi child” who experienced viral rebound after more than 2 years off ART, additional immunomodulatory strategies might be required for sustained viral suppression after ART cessation. In this review, we discuss the interactions between HIV and the developing immune system in children and the potential implications for therapeutic and prophylactic interventions.